Dependence of Quantum Yield for Periodic Array of Doped Semiconductor Nanocrystals (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied and calculated the fraction of empty semiconductor nanocrystals  which controls the quantum yield as a function of the average number of donors per  nanocrystal and the nanocrystal size. We have shown that if donor reached the  critical value of 1.8 there are no empty nanocrystals in nanocrystal array due to  electron redistribution between nanocrystals and consequently photoluminescence  vanishes. The relative intensity of the photoluminescence is strongly correlated with  the transport properties of these array. Which provides information about the  redistribution of the charges between nanocrystals affecting both quantum yield of  photoluminescence of an array of nanocrystals and its hopping conductivity. We  have found that empty nanocrystals became extinct and photoluminescence was  quenched abruptly at an average number of donors per nanocrystal. It turned out  that doping resulted in transport properties which were typical for disordered  semiconductors. The number of donors in different nanocrystals was random. In the  ground state of the nanocrystal array many nanocrystals were charged. The charged  nanocrystals leaded to the random coulomb potential and to the coulomb gap in the  density of localized electron states that determined variable range of hopping  conductivity. It was also found that an array of small nanocrystals due to the  quantuization-gap induced redistribution of electrons among nanocrystals. The  obtained results were found in good agreement with previous results.